Charcoal production using tropical pine thinnings - Pontinha, Ananias de Almeida Saraiva; Veiga, Ricardo Antonio de Arruda; Leão, Alcides Lopes [UNESP] (Elsevier, 1992)
In Brazil, the wood from pine-plantation thinnings is difficult to sell. However, these wood thinnings could be used to produce charcoal. The physical and chemical properties of charcoal produced from logs or first and fourth thinnings of Pinus caribaea var. hondurensis and Pinus oocarpa were determined. Similar properties were also determined for sawmill slabs cut from first and fourth thinnings. Properties were compared to charcoal made from pine materials and 7-yr-old Eucalyptus grandis. Results show that Pinus spp had better chemical properties than did E. grandis. In contrast, charcoal obtained from E. grandis had higher values of apparent density and lower values of bulk density than did Pinus spp. © 1992.
Keywords: charcoal production; energy source; pine plantation; wood thinnings; Brazil